STATUS HUKUM ANAK DILUAR NIKAH - Nur Puat (LPPM Institut Agama Islam Al-Hikmah Tuban, 2013)
According to Islamic law, children out of wedlock have only lineage relationship with her mother and her mother's family, since they only lineage and inheritance with his mother and his mother's family. According to the laws of marriage and the compilation of Islamic law, states that a child outside of marriage has only civil relationship with her mother and her mother's family. According to the Civil Code, states that a child outside of marriage, except those born of adultery or contamination of blood, was passed by the subsequent marriage of their father and mother, before marriage if they have legal recognition of the child, or if it occurred in the recognition her own marriage certificate. According to the decision of the constitutional court, a child born outside marriage have a civil relationship with her mother and her mother's family as well as with men as her father can be proved by science and technology, and/or other evidence under the law to have blood relations, including civil relations with his father's family.